2018
DOI: 10.1126/sciadv.aau9366
|View full text |Cite
|
Sign up to set email alerts
|

Graphene catalyzes the reversible formation of a C–C bond between two molecules

Abstract: Graphene grown on a transition metal surface catalyzes a reversible C–C bond–forming reaction between two molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…In particular, the on-surface migration of the spherical intermediate as depicted in Figure c can be directly correlated to an increased hydrogen loss rate (highlighted in Figure a). This dynamic bond breaking and binding to the GML catalyzes the H loss significantly and makes graphene a non-innocent substrate in our observations . This finding is important because previous SMART-EM studies revealed that molecules encapsulated in carbon nanotubes, , or attached to the periphery of carbon nanohorns, ,, show only minor interactions with the substrate.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…In particular, the on-surface migration of the spherical intermediate as depicted in Figure c can be directly correlated to an increased hydrogen loss rate (highlighted in Figure a). This dynamic bond breaking and binding to the GML catalyzes the H loss significantly and makes graphene a non-innocent substrate in our observations . This finding is important because previous SMART-EM studies revealed that molecules encapsulated in carbon nanotubes, , or attached to the periphery of carbon nanohorns, ,, show only minor interactions with the substrate.…”
Section: Resultssupporting
confidence: 50%
“…This dynamic bond breaking and binding to the GML catalyzes the H loss significantly and makes graphene a noninnocent substrate in our observations. 51 This finding is important because previous SMART-EM studies revealed that molecules encapsulated in carbon nanotubes, 52,53 or attached to the periphery of carbon nanohorns, 15,54,55 show only minor interactions with the substrate. Even though the hydrogen atoms' contributions are neglectable to the overall contrast of the molecule in TEM, their presence (or absence) has a great impact on the overall geometry of the structure.…”
mentioning
confidence: 94%
“…Moiré patterns represent a gradual change in the interaction between the film and the substrate across its unit cell, giving rise to a spatial modulation of the reactivity at the atomic level. This effect was demonstrated for graphene and opens new possibilities for catalysis on 2D materials . In thin film silica systems, a moiré pattern was reported for a silica ML on Ru(0001).…”
Section: Resultsmentioning
confidence: 78%
“…This effect was demonstrated for graphene 26 and opens new possibilities for catalysis on 2D materials. 27 In thin film silica systems, a moirépattern was reported for a silica ML on Ru(0001). In this case, a 30°F rotation after annealing triggered the emergence of the longrange spatial modulation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The electron buzzing around the carbon atom which interact with the periodic potential of graphene hexagonal lattice [12] which produce new quasi-particles that's why graphene never stop conducting. The reasons that makes graphene interesting both as individual and as composites is due to the outstanding properties such as stiffness, strength [13] and toughness [14]. Throughout the world research groups working on the development of industrially fabricated graphene layers that have high stiffness used as graphene based composites for optoelectronics and neural implants [15,16].…”
Section: Introductionmentioning
confidence: 99%